The Development of Instructional Specimens for Studying the Effect of Welding Parameters - Bootchai, Suparat; Khamdaeng, Thawatchai; Kaewsakul, Nut; Sonsanam, Anyarat; Angboonta, Parvinee (Journal of Technical and Engineering Education, 2024)
Welding is very important in construction and various industries, leading to a high demand for skilled welders, which in turn requires knowledgeable and skilled welding instructors. Quality welding instructors can accurately and thoroughly teach welding knowledge and skills, giving students a good foundation for their careers. Although previous research has studied the effect of welding parameters i.e., welding currents and travel speed, there are still limited educational materials on welding. This research aims to develop instructional specimens and teaching materials for studying the effect of welding parameters made by Gas Metal Arc Welding (GMAW) using welding robots. The quality, the learning outcome and the satisfaction of these instructional specimens and teaching materials were evaluated. The research tools include the creation of instructional specimens using welding currents of 190A, 210A, and 250A, and travel speeds of 3.0, 3.5 and 4.0mm/s, with constant welding voltage and contact tip to work distance (CTWD) and using carbon dioxide gas for shielding. Additionally, there are lesson plans, teaching materials, and exercises. The research sample consisted of 15 first-year students in the Industrial Engineering program of the Faculty of Technical Education. Data were analyzed using mean, standard deviation, and t-test (Dependent). The research results showed that the quality of the instructional specimens and teaching materials for studying the effect of welding parameters had an overall mean of 4.18 (S.D.=0.71), indicating good quality. When analyzing each part, the measurement and evaluation scored highest, followed by content, and then the instructional specimens with teaching materials. The learning outcomes showed that post-test was significantly higher than pre-test, with statistical significance at the 0.05 level. Additionally, the overall satisfaction of students on instructional specimens and teaching materials was very high ( 𝑥̅ =4.51, S.D.=0.68).